A novel multivariate scoring system for determining the prognosis of lymph node-negative esophageal squamous cell carcinoma following surgical therapy: An observational study. Issue 4 (April 2015) - Ma, G.; Zhang, X.; Ma, Q.; Rong, T.; Long, H.; Lin, P.; Fu, J.; Zhang, L.
Abstract Background Identifying patients with esophageal squamous cell carcinoma (ESCC) with negative prognostic factors, which have an extremely low survival rate, has been problematic. Methods We retrospectively collected clinical data for 648 patients with lymph node-negative ESCC who were treated at the Sun Yat-Sen University Cancer Center from 1990 to 2005. Survival difference was compared using Kaplan–Meier analysis and multivariate Cox regression analysis. Results We identified advancing age, smoking history, alcohol consumption history, decreased forced expiratory volume in 1 s (FEV1), surgical procedure, tumor location, number of resected lymph nodes, poor tumor differentiation, and surgical stage as independent prognostic risk factors. Furthermore, based on the results of multivariate analysis, we constructed a novel scoring system that included the factors of age, smoking history, alcohol consumption history, number of resected lymph nodes, tumor differentiation, and surgical stage. Risk score (RS) was computed with the scoring system, and patients were divided into Class A (RS: 0–5) and Class B (RS: 6–10). P < 0.001 indicated statistical significance. A significant difference (p < 0.001) demonstrated that Class B was strongly related to a low survival rate and poor prognosis. Conclusion We developed a new simple flexible scoring system of high prognostic significance, which has the potential to guide postoperative therapeutic strategies and follow-up frequency and to provide better prognostic information for patients and their families.